Permasalahan Pengasuhan di Era Digital: Suara Orang Tua dan Harapan terhadap Literasi Digital - Cholimah, Nur; Setyaningsih, Adinda; Hunaerni, Faadhilah Augustin; Hanum, Aliyah Latifah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The rapid development of digital technology has had a significant impact on parenting patterns within families. This study aims to identify the parenting challenges faced by parents in the digital age and explore their expectations regarding digital literacy training. The study employs a descriptive quantitative approach using a survey technique targeting 67 parents at a preschool institution participating in digital literacy activities. Data was collected through a questionnaire containing closed and open-ended questions. The results of the study indicate that most parents face challenges in accompanying children who use gadgets too frequently, as well as difficulties in fostering discipline, responsibility, and emotional management in children. As many as 55.2% of respondents admitted they had never received clear digital literacy materials. Parents' expectations for digital literacy training encompass five main themes: increasing knowledge and understanding (40.7%), obtaining concrete solutions and strategies (20.3%), positive changes in children (13.6%), strengthening the role of parents (10.2%), and personal transformation (15.3%). These findings highlight the urgency of strengthening family-based digital literacy, so that parents can wisely and effectively guide their children in navigating the challenges of the digital world.